CipA of Acinetobacter baumannii is a novel plasminogen binding and complement inhibitory protein - Koenigs, Arno; Wallich, Reinhard (The journal of infectious diseases, 2016)
Abstract. Acinetobacter baumannii is an emerging opportunistic pathogen, responsible for up to 10% of gram-negative, nosocomial infections. The global increase
Published online 17 December 2015
Gesehen am 15.10.2019
Im Titel ist "Acinetobacter baumannii" kursiv geschrieben